SOCIAL RISK – AGGRESSIVE BEHAVIOR OF CHILDREN - Кудрявицька, Аліна; Карабач, Катерина (Modern engineering and innovative technologies, 2023)
Providing of emotional comfort of child is basis of her normal psychical development, guarantee of increase of personality that will live in harmony with a soba and surrounding world, will perfect itself, enjoy intermingling with the persons of the same a